(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Аннотация: Данная статья посвящена анализу деривационных цепей в русском языке как системного проявления словообразовательных процессов. Рассматриваются принципы построения, основные типы и функциональное значение деривационных цепей. Особое внимание уделяется выявлению взаимодействия между элементами цепи, их иерархической организации и динамике в контексте эволюции языковой системы и когнитивных механизмов номинации. This paper analyzes derivational chains in the Russian language as a systemic manifestation of word-formation processes. It examines the principles of their construction, main types, and functional significance. Special attention is given to identifying the interaction between the chain elements, their hierarchical organization, and their dynamics within the context of the evolution of the language system and cognitive mechanisms of nomination.